STUDI DESKRIPTIF SEBUKU PADA ADA BEGURU DALAM RITUALPERNIKAHANDIDESAKUTELINTANG,KECAMATAN BUKIT, KABUPATEN BENER MERIAH: Descriptive Study of Sebuku in Ada Beguru during the Wedding Ritual in Kute Lintang Village, Bukit District, Bener Meriah Regency - ati, sumi; Ocktarizka , Tria; Anwar, Humaira (Awilaras, 2024)
This research is entitled "Sebuku Descriptive Study on the Beguru Custom in Wedding Rituals in Kute Lintang Village, Bukit District, Bener Meriah Regency". What the author examines in this research is the structure of the Sebuku Song in the Beguru Custom in Wedding Rituals in Kute Lintang Village, Bukit District, Bener Meriah Regency. The aim of this research is to examine the structure of the Sebuku Song in the Beguru Custom in Wedding Rituals in Kute Lintang Village, Bukit District, Bener Meriah Regency. This research uses qualitative research with a descriptive approach. Data obtained using observation, interview and documentation techniques. Data analysis techniques use data reduction, data presentation and data verification. The theory used in this research is the theory of Jamalus and Bruno Natlle. Jamalus states that song structure is the arrangement and relationship between musical elements in a song, and to strengthen the ideas of Jamalus' theory, researchers also use Bruno Natlle's theory, to analyze song structure using the following elements: repertory, scales, tonality, intervals, melodic structure, rhythm, tempo and form. Sebuku in the beguru tradition is done in the morning, wearing upuh ulen-ulen and sitting on the ampang before the marriage ceremony is carried out. The conclusion of this research is that the song structure of the book has musical elements as stated by Bruno Nattle. Of the eight musical elements, only rhythm is not present in the song, because the book is not based on and is not tied to rhythm, but of the s even elements- These elements exist in a book but are not bound and are still changing.